High-durability composite proton exchange membrane and preparation method thereof
By introducing coating of whole fluorine sulfonic acid resin, inorganic free radicals, and organic antioxidants in the proton exchange film, combined with the enhanced layer of plasma treatment, the problem of the proton switching membrane is susceptible to chemical degradation in electrolytic hydrogenation , Significantly improved its durability and performance.
Patent Information
- Application Number
- CN202411322917.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-21
AI Technical Summary
In the proton exchange membrane electrolyzes water for hydrogen production, the proton exchange membrane is prone to chemical degradation during long-term operation and recycling, resulting in reduced performance or failure, and durability problems.
A composite proton exchange film includes an enhanced layer and coating. The coating consists of a full fluorosamulfonic acid resin, inorganic free radicals, and organic antioxidants. Essence
The chemical durability of the composite proton exchange membrane is significantly improved, its stability and performance in the process of electrolyzing water for hydrogen production are enhanced, and the service life of the membrane is extended.
Smart Images

Figure CN119332301A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogen production by electrolysis of water using a proton exchange membrane, and relates to a perfluorosulfonic acid composite proton exchange membrane and a preparation method thereof, wherein the proton exchange membrane has high durability. Background Art
[0002] Proton exchange membrane water electrolysis is an emerging hydrogen production technology that is receiving more and more attention. Compared with traditional water electrolysis hydrogen production technology, proton exchange membrane water electrolysis has the advantages of fast start-up and high energy conversion efficiency, thus matching the volatility of renewable energy generation, and gradually becoming the mainstream technology for hydrogen production. The working principle of proton exchange membrane water electrolysis is relatively simple. First, water molecules undergo oxidation reaction under the catalytic action of the anode catalyst to generate oxygen and hydrogen ions. Then the hydrogen ions pass through the proton exchange membrane to the cathode side, and hydrogen is generated under the action of the cathode catalyst.
[0003] As one of the key components of proton exchange membrane electrolysis for hydrogen production, proton exchange membrane plays the role of proton conduction, gas separation and electron blocking. However, the durability of proton exchange membrane electrolysis in long-term operation is still one of the challenges. During long-term operation and continuous recycling, the proton exchange membrane often suffers from chemical degradation due to the attack of free radicals generated during the operation of the electrolyzer, resulting in performance degradation or even failure. Therefore, it is urgent to find a solution that can effectively solve the problem of chemical degradation. Summary of the invention
[0004] The purpose of the present invention is to provide a composite proton exchange membrane and a preparation method thereof, so as to solve the problem of poor chemical durability of proton exchange membranes used in the prior art for hydrogen production by electrolysis of water. The above-mentioned purpose of the present invention is achieved by the following technical solutions:
[0005] A first aspect of the present invention relates to a composite proton exchange membrane, comprising: a reinforcement layer and a coating layer, wherein the coating layer is formed on at least one side of the reinforcement layer and comprises a perfluorosulfonic acid resin, an inorganic free radical quencher, and an organic antioxidant.
[0006] Preferably, the inorganic free radical quencher comprises a carboxylated inorganic free radical quencher, and the organic antioxidant comprises an organic antioxidant having an amino group.
[0007] Preferably, the inorganic free radical quencher includes one or more of carboxy cerium dioxide and carboxy manganese dioxide, and the organic antioxidant includes one or more of 4,4'-diamino-2,2'-bipyridine and 3,4-dihydroxyphenylalanine.
[0008] Preferably, the molar ratio between the inorganic free radical quencher and the organic antioxidant is 1:(0.2 to 3).
[0009] Preferably, the total mass of the inorganic free radical quencher and the organic antioxidant is 0.02 g to 0.5 g per 10 g of the perfluorosulfonic acid resin.
[0010] Preferably, the reinforcement layer is plasma treated, and the reinforcement layer includes one of polyetheretherketone (PEEK), polytetrafluoroethylene (PTFE), and polyphenylene sulfide (PPS).
[0011] The second aspect of the present invention relates to a method for preparing a composite proton exchange membrane, comprising: providing a coating, the coating comprising a perfluorosulfonic acid resin, an inorganic free radical quencher, and an organic antioxidant; applying the coating to at least one side of a reinforcement layer; and drying and annealing the coating applied to the reinforcement layer to form a coating.
[0012] Preferably, the preparation of the coating comprises: mixing the inorganic free radical quencher with a first solvent to obtain a mixed solution; mixing the organic antioxidant with the mixed solution; drying the mixed solution containing the organic antioxidant to obtain an additive; mixing the perfluorosulfonic acid resin with a second solvent to obtain a perfluorosulfonic acid solution; and mixing the additive with the perfluorosulfonic acid solution to obtain the coating.
[0013] Preferably, before applying the coating to the reinforcing layer, the method further comprises: treating the reinforcing layer with plasma, wherein the plasma treatment time is 50s to 500s, the power is 50W to 300W, the introduced gas is nitrogen, and the gas flow rate is 50mL / min to 200mL / min.
[0014] Preferably, the drying temperature is 60° C. to 100° C., and the time is 30 min to 120 min. The annealing temperature is 100° C. to 160° C., and the time is 30 min to 120 min.
[0015] Compared with the prior art, the present invention has one or more of the following advantages:
[0016] 1. The preparation method of the present invention is simple. The composite proton exchange membrane only needs to be prepared by mixing perfluorosulfonic acid resin with additives and then coating them on a reinforcement layer. The preparation process of the additives is simple, which lays a solid foundation for large-scale production.
[0017] 2. The additives used have good free radical scavenging effects, and the inorganic free radical quencher and the organic antioxidant work simultaneously, greatly improving the chemical durability of the composite proton membrane. In addition, the carboxylated inorganic free radical quencher and the organic antioxidant with an amino group are chemically combined, are not easy to decompose, and can be stably present in the composite proton membrane.
[0018] 3. Adding an appropriate amount of the additives used into the composite membrane can increase the water absorption rate of the composite membrane and provide additional proton transmission channels, thereby increasing the proton conductivity of the composite membrane.
[0019] 4. The reinforcement layer used is treated with plasma to improve the adhesion and hydrophilicity of the reinforcement layer, thereby improving the bonding effect between the coating and the reinforcement layer, making the bonding closer and with fewer defects. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is a cross-sectional schematic diagram showing the composite proton exchange membrane mentioned in the first embodiment of the present invention;
[0021] Figure 2 It is a cross-sectional scanning electron microscope (SEM) image showing the proton exchange membrane prepared in Comparative Example 1. DETAILED DESCRIPTION
[0022] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0023] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0024] Please refer to Figure 1 , presenting the composite proton exchange membrane mentioned in the first embodiment of the present invention, comprising: a reinforcement layer (1) and a coating (2), wherein the coating (2) is formed on at least one side of the reinforcement layer (1), and the coating (2) comprises a perfluorosulfonic acid resin, an inorganic free radical quencher, and an organic antioxidant. The coating (2) can be formed on one side or both sides of the reinforcement layer (1), preferably formed on both sides of the reinforcement layer (1).
[0025] First, the reinforcing layer (1) is discussed. The reinforcing layer (1) may be, but is not limited to, plasma treated, and the conditions of the plasma treatment may include, but are not limited to: a time of 50s to 500s, a power of 50W to 300W, nitrogen gas, and a gas flow rate of 50mL / min to 200mL / min. In addition, the time of the plasma treatment is preferably 50s, 75s, 100s, 125s, 150s, 175s, 200s, 225s, 250s, 275s, 300s, 325s, 350s, 375s, 400s, 425s, 450s, 475s, or 500s; the power of the plasma treatment is preferably 50W, 75W, 100W, 125W, 150W, 175W, 200W, 225W, 250W, 275W, or 30 0W; the gas flow rate of the plasma treatment is preferably 50mL / min, 60mL / min, 70mL / min, 80mL / min, 90mL / min, 100mL / min, 110mL / min, 120mL / min, 130mL / min, 140mL / min, 150mL / min, 160mL / min, 170mL / min, 180mL / min, 190mL / min, or 200mL / min. In addition, the reinforcing layer (1) may include but is not limited to one of polyetheretherketone (PEEK), polytetrafluoroethylene (PTFE), and polyphenylene sulfide (PPS).
[0026] Next, the coating (2) is discussed. The inorganic free radical quencher and the organic antioxidant may be chemically bonded, but not limited to. The inorganic free radical quencher may include, but not limited to, carboxylated inorganic free radical quenchers, preferably including one or more of carboxylated cerium dioxide and carboxylated manganese dioxide; the organic antioxidant may include, but not limited to, an organic antioxidant with an amino group, preferably including one or more of 4,4'-diamino-2,2'-bipyridine and 3,4-dihydroxyphenylalanine. In addition, the molar ratio between the inorganic free radical quencher and the organic antioxidant may be, but not limited to, 1:(0.2 to 3), preferably 1:0.2, 1:0.4, 1:0.6, 1:0.8, 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2, 1:2.2, 1:2.4, 1:2.6, 1:2.8, or 1:3. Furthermore, relative to every 10g of perfluorosulfonic acid resin, the total mass of the inorganic free radical quencher and the organic antioxidant may be but is not limited to 0.02g to 0.5g, preferably 0.02g, 0.04g, 0.06g, 0.08g, 0.1g, 0.12g, 0.14g, 0.16g, 0.18g, 0.2g, 0.22g, 0.24g, 0.26g, 0.28g, 0.3g, 0.32g, 0.34g, 0.36g, 0.38g, 0.4g, 0.42g, 0.44g, 0.46g, 0.48g, or 0.5g.
[0027] Please refer to the following, which describes the preparation method of the composite proton exchange membrane mentioned in the second embodiment of the present invention. It should be noted that the second embodiment can be used to prepare the composite proton exchange membrane mentioned in the first embodiment, and can also be used to prepare other composite proton exchange membranes not mentioned; that is, the composite proton exchange membrane mentioned in the first embodiment should not be limited by the content mentioned in the second embodiment.
[0028] First, a coating is provided, the coating comprising a perfluorosulfonic acid resin, an inorganic free radical quencher, and an organic antioxidant. It should be noted that the description of the perfluorosulfonic acid resin, the inorganic free radical quencher, and the organic antioxidant mentioned in the second embodiment can refer to the first embodiment unless otherwise specified.
[0029] The preparation of the coating may include but is not limited to: mixing an inorganic free radical quencher with a first solvent to obtain a mixed solution; mixing an organic antioxidant with the mixed solution; drying the mixed solution containing the organic antioxidant to obtain an additive; mixing a perfluorosulfonic acid resin with a second solvent to obtain a perfluorosulfonic acid solution; and mixing the additive with the perfluorosulfonic acid solution to obtain the coating.
[0030] The first solvent may include but is not limited to one or more of water and ethanol; under the condition that the first solvent includes water and ethanol, the mass ratio between water and ethanol may be but is not limited to 1: (0.5 to 2), preferably 1: 0.5, 1: 1, 1: 1.5, or 1: 2. In addition, the molar number of the inorganic free radical quencher per 100 mL of the first solvent may be but is not limited to 0.5 mmol to 10 mmol, preferably 0.5 mmol, 1 mmol, 2 mmol, 3 mmol, 4 mmol, 5 mmol, 6 mmol, 7 mmol, 8 mmol, 9 mmol, or 10 mmol.
[0031] Mixing the organic antioxidant with the mixed solution may include but is not limited to: adding the organic antioxidant to the mixed solution; and stirring the mixed solution containing the organic antioxidant. In addition, the molar number of the organic antioxidant relative to each 100mL of the first solvent may be but is not limited to 0.5mmol to 10mmol, preferably 0.5mmol, 1mmol, 2mmol, 3mmol, 4mmol, 5mmol, 6mmol, 7mmol, 8mmol, 9mmol, or 10mmol. In addition, stirring the mixed solution containing the organic antioxidant may be carried out at but is not limited to 50℃ to 75℃, preferably 50℃, 55℃, 60℃, 65℃, 70℃, or 75℃; the stirring time may be but is not limited to 6h to 18h, preferably 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, or 18h.
[0032] Drying the mixed solution containing the organic antioxidant to obtain the additive can be carried out at, but not limited to, 50°C to 75°C, preferably 50°C, 55°C, 60°C, 65°C, 70°C, or 75°C; the drying time can be, but not limited to, 0.5h to 6h, preferably 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, or 6h. Since the so-called "additive" contains an inorganic free radical quencher and an organic antioxidant, in order to improve the purity of the additive, before drying the mixed solution containing the organic antioxidant to obtain the additive, it can also include, but is not limited to: centrifuging the mixed solution containing the organic antioxidant; and filtering and washing the precipitate obtained by centrifugation with water. The centrifugal speed may be, but not limited to, 3000 r / min to 7000 r / min, preferably 3000 r / min, 4000 r / min, 5000 r / min, 6000 r / min, or 7000 r / min; the centrifugal time may be, but not limited to, 5 min to 15 min, preferably 5 min, 7.5 min, 10 min, 12.5 min, or 15 min.
[0033] The second solvent may include but is not limited to one or more of water, n-propanol, and N,N-dimethylformamide; under the condition that the second solvent includes water, n-propanol, and N,N-dimethylformamide, based on the total mass of the second solvent, water may account for but is not limited to 30wt% to 50wt%, preferably 30wt%, 35wt%, 40wt%, 45wt%, or 50wt%; n-propanol may account for but is not limited to 30wt% to 50wt%, preferably 30wt%, 35wt%, 40wt%, 45wt%, or 50wt%; N,N-dimethylformamide may account for but is not limited to 10wt% to 30wt%, preferably 10wt%, 15wt%, 20wt%, 25wt%, or 30wt%. Based on the total mass of the perfluorosulfonic acid solution, the perfluorosulfonic acid resin may account for but is not limited to 10wt% to 50wt%, preferably 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, or 50wt%.
[0034] Mixing the additive with the perfluorosulfonic acid solution to obtain the coating may include but is not limited to: adding the additive to the perfluorosulfonic acid solution; and ultrasonically oscillating the perfluorosulfonic acid solution containing the additive. The mass of the additive (the total mass of the inorganic free radical quencher and the organic antioxidant) relative to every 100g of the perfluorosulfonic acid solution may be but is not limited to 0.1g to 1g, preferably 0.1g, 0.2g, 0.3g, 0.4g, 0.5g, 0.6g, 0.7g, 0.8g, 0.9g, or 1g. The purpose of ultrasonic oscillation is to uniformly disperse the additive in the perfluorosulfonic acid solution; and the time of ultrasonic oscillation may be but is not limited to 20min to 40min, preferably 20min, 25min, 30min, 35min, or 40min.
[0035] Next, the coating is applied to at least one side of a reinforcement layer. It should be noted that the description of the reinforcement layer mentioned in the second embodiment can refer to the first embodiment unless otherwise specified. Before the coating is applied to the reinforcement layer, it may further include but is not limited to: treating the reinforcement layer with plasma, the plasma treatment time is 50s to 500s, the power is 50W to 300W, the gas is nitrogen, and the gas flow rate is 50mL / min to 200mL / min. In addition, the plasma treatment time is preferably 50 s, 75 s, 100 s, 125 s, 150 s, 175 s, 200 s, 225 s, 250 s, 275 s, 300 s, 325 s, 350 s, 375 s, 400 s, 425 s, 450 s, 475 s, or 500 s; the plasma treatment power is preferably 50 W, 75 W, 100 W, 125 W, 150 W, 175 W, 200 W, 225 W, 250 W, 275 W, or 30 0W; the gas flow rate for plasma treatment is preferably 50mL / min, 60mL / min, 70mL / min, 80mL / min, 90mL / min, 100mL / min, 110mL / min, 120mL / min, 130mL / min, 140mL / min, 150mL / min, 160mL / min, 170mL / min, 180mL / min, 190mL / min, or 200mL / min.
[0036] Finally, the coating applied to the reinforcing layer is dried and annealed to form a coating. The drying temperature may be, but not limited to, 60°C to 100°C, preferably 60°C, 70°C, 80°C, 90°C, or 100°C; the drying time may be, but not limited to, 30min to 120min, preferably 30min, 40min, 50min, 60min, 70min, 80min, 90min, 100min, 110min, or 120min. The annealing temperature may be, but not limited to, 100°C to 160°C, preferably 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, or 160°C; the annealing time may be, but not limited to, 30min to 120min, preferably 30min, 40min, 50min, 60min, 70min, 80min, 90min, 100min, 110min, or 120min.
[0037] It should be noted that under the condition of forming multiple coating layers, it is not limited to applying the coating to the reinforcing layer, drying and annealing the coating applied to the reinforcing layer to form one coating layer, and then repeating the coating, drying and annealing to form another coating layer. In fact, the coating can be applied to the reinforcing layer and dried, and then the coating can be applied to the reinforcing layer and dried again until a predetermined thickness is reached, and then annealed again to form multiple coating layers.
[0038] The present invention is illustrated by the following examples:
[0039] Example 1
[0040] The preparation of the proton exchange membrane of this embodiment is as follows:
[0041] (1) Weigh 1 mmol of carboxy cerium dioxide and add it to 100 ml of ethanol aqueous solution with a mass ratio of 1:1, stir until dissolved, and obtain a mixed solution. Weigh 1 mmol of 4,4'-diamino-2,2'-bipyridine and add it to the mixed solution, heat it in a 60°C water bath, stir it for 12 hours, and then centrifuge it at a centrifugal speed of 5000 r / min for 10 minutes, then filter it and wash it with water for 3 times, and finally dry it at 60°C for 2 hours to obtain an additive.
[0042] (2) Add 10 g of perfluorosulfonic acid resin to a mixed solvent of 6 g of water, 6 g of n-propanol, and 3 g of N,N-dimethylformamide, and stir for 24 h to obtain a uniform perfluorosulfonic acid solution. Add 0.1 g of the additive to the perfluorosulfonic acid solution, stir for 12 h, and then place it in an ultrasonic cleaning machine for 30 min to disperse it evenly, thereby obtaining a perfluorosulfonic acid resin solution containing the additive.
[0043] (3) The reinforced layer polyetheretherketone (PEEK) mesh was placed in a plasma cleaning machine for treatment. The treatment time was 100 s, the power was 100 W, the gas was nitrogen, and the gas flow rate was 200 mL / min.
[0044] (4) The perfluorosulfonic acid resin solution containing the additive is placed in a coating machine for the first coating, followed by bonding to a polyetheretherketone (PEEK) mesh cloth, drying at 60°C for 30 minutes, and then coating for the second time, drying at 60°C for 30 minutes, annealing at 130°C for 1 hour, and naturally cooling to obtain a proton exchange membrane.
[0045] Example 2
[0046] The preparation of the proton exchange membrane of this embodiment is as follows:
[0047] (1) Weigh 1 mmol of carboxy cerium dioxide and add it to 100 ml of ethanol aqueous solution with a mass ratio of 1:1, stir until dissolved, and obtain a mixed solution. Weigh 1 mmol of 3,4-dihydroxyphenylalanine and add it to the mixed solution, heat it in a 60°C water bath, stir it for 12 hours, and then centrifuge it at a centrifugal speed of 5000 r / min for 10 minutes, then filter it and wash it with water for 3 times, and finally dry it at 60°C for 2 hours to obtain an additive.
[0048] (2) Add 10 g of perfluorosulfonic acid resin to a mixed solvent of 6 g of water, 6 g of n-propanol, and 3 g of N,N-dimethylformamide, and stir for 24 h to obtain a uniform perfluorosulfonic acid solution. Add 0.1 g of the additive to the perfluorosulfonic acid solution, stir for 12 h, and then place it in an ultrasonic cleaning machine for 30 min to disperse it evenly, thereby obtaining a perfluorosulfonic acid resin solution containing the additive.
[0049] (3) The reinforced layer polyetheretherketone (PEEK) mesh was placed in a plasma cleaning machine for treatment. The treatment time was 100 s, the power was 100 W, the gas was nitrogen, and the gas flow rate was 200 mL / min.
[0050] (4) The perfluorosulfonic acid resin solution containing the additive is placed in a coating machine for the first coating, followed by bonding to a polyetheretherketone (PEEK) mesh cloth, drying at 60°C for 30 minutes, and then coating for the second time, drying at 60°C for 30 minutes, annealing at 130°C for 1 hour, and naturally cooling to obtain a proton exchange membrane.
[0051] Example 3
[0052] The preparation of the proton exchange membrane of this embodiment is as follows:
[0053] (1) Weigh 1 mmol of carboxyl manganese dioxide and add it to 100 ml of ethanol aqueous solution with a mass ratio of 1:1, stir until dissolved, and obtain a mixed solution. Weigh 1 mmol of 4,4'-diamino-2,2'-bipyridine and add it to the mixed solution, heat it in a 60°C water bath, stir it for 12 hours, and then centrifuge it at a centrifugal speed of 5000 r / min for 10 minutes, then filter it and wash it with water for 3 times, and finally dry it at 60°C for 2 hours to obtain an additive.
[0054] (2) Add 10 g of perfluorosulfonic acid resin to a mixed solvent of 6 g of water, 6 g of n-propanol, and 3 g of N,N-dimethylformamide, and stir for 24 h to obtain a uniform perfluorosulfonic acid solution. Add 0.1 g of the additive to the perfluorosulfonic acid solution, stir for 12 h, and then place it in an ultrasonic cleaning machine for 30 min to disperse it evenly, thereby obtaining a perfluorosulfonic acid resin solution containing the additive.
[0055] (3) The reinforced layer polyetheretherketone (PEEK) mesh was placed in a plasma cleaning machine for treatment. The treatment time was 100 s, the power was 100 W, the gas was nitrogen, and the gas flow rate was 200 mL / min.
[0056] (4) The perfluorosulfonic acid resin solution containing the additive is placed in a coating machine for the first coating, followed by bonding to a polyetheretherketone (PEEK) mesh cloth, drying at 60°C for 30 minutes, and then coating for the second time, drying at 60°C for 30 minutes, annealing at 130°C for 1 hour, and naturally cooling to obtain a proton exchange membrane.
[0057] Example 4
[0058] The preparation of the proton exchange membrane of this embodiment is as follows:
[0059] (1) Weigh 1 mmol of carboxy manganese dioxide and add it to 100 ml of ethanol aqueous solution with a mass ratio of 1:1, stir until dissolved, and obtain a mixed solution. Weigh 1 mmol of 3,4-dihydroxyphenylalanine and add it to the mixed solution, heat it in a 60°C water bath, stir it for 12 hours, and then centrifuge it at a centrifugal speed of 5000 r / min for 10 minutes, then filter it and wash it with water for 3 times, and finally dry it at 60°C for 2 hours to obtain an additive.
[0060] (2) Add 10 g of perfluorosulfonic acid resin to a mixed solvent of 6 g of water, 6 g of n-propanol, and 3 g of N,N-dimethylformamide, and stir for 24 h to obtain a uniform perfluorosulfonic acid solution. Add 0.1 g of the additive to the perfluorosulfonic acid solution, stir for 12 h, and then place it in an ultrasonic cleaning machine for 30 min to disperse it evenly, thereby obtaining a perfluorosulfonic acid resin solution containing the additive.
[0061] (3) The reinforced layer polyetheretherketone (PEEK) mesh was placed in a plasma cleaning machine for treatment. The treatment time was 100 s, the power was 100 W, the gas was nitrogen, and the gas flow rate was 200 mL / min.
[0062] (4) The perfluorosulfonic acid resin solution containing the additive is placed in a coating machine for the first coating, followed by bonding to a polyetheretherketone (PEEK) mesh cloth, drying at 60°C for 30 minutes, and then coating for the second time, drying at 60°C for 30 minutes, annealing at 130°C for 1 hour, and naturally cooling to obtain a proton exchange membrane.
[0063] Comparative Example 1
[0064] The preparation of the proton exchange membrane of this comparative example is as follows:
[0065] (1) Add 10 g of perfluorosulfonic acid resin to a mixed solvent of 6 g of water, 6 g of n-propanol, and 3 g of N,N-dimethylformamide, and stir for 24 h to obtain a uniform perfluorosulfonic acid solution.
[0066] (2) The reinforced layer polyetheretherketone (PEEK) mesh was placed in a plasma cleaning machine for treatment. The treatment time was 100 s, the power was 100 W, the gas was nitrogen, and the gas flow rate was 200 mL / min.
[0067] (3) The perfluorosulfonic acid resin solution is placed in a coating machine for the first coating, followed by bonding to a polyetheretherketone (PEEK) mesh cloth, drying at 60°C for 30 minutes, and then coating for the second time, drying at 60°C for 30 minutes, annealing at 130°C for 1 hour, and naturally cooling to obtain a proton exchange membrane.
[0068] Comparative Example 2
[0069] The preparation of the proton exchange membrane of this comparative example is as follows:
[0070] (1) Weigh 1 mmol of carboxy cerium dioxide and add it to 100 ml of ethanol water solution with a mass ratio of 1:1, stir until dissolved, and obtain a mixed solution. Then centrifuge at a centrifugal speed of 5000 r / min for 10 minutes, then filter and wash with water for 3 times, and finally dry at 60°C for 2 hours to obtain an additive.
[0071] (2) Add 10 g of perfluorosulfonic acid resin to a mixed solvent of 6 g of water, 6 g of n-propanol, and 3 g of N,N-dimethylformamide, and stir for 24 h to obtain a uniform perfluorosulfonic acid solution. Add 0.1 g of the additive to the perfluorosulfonic acid solution, stir for 12 h, and then place it in an ultrasonic cleaning machine for 30 min to disperse it evenly, thereby obtaining a perfluorosulfonic acid resin solution containing the additive.
[0072] (3) The reinforced layer polyetheretherketone (PEEK) mesh was placed in a plasma cleaning machine for treatment. The treatment time was 100 s, the power was 100 W, the gas was nitrogen, and the gas flow rate was 200 mL / min.
[0073] (4) The perfluorosulfonic acid resin solution containing the additive is placed in a coating machine for the first coating, followed by bonding to a polyetheretherketone (PEEK) mesh cloth, drying at 60°C for 30 minutes, and then coating for the second time, drying at 60°C for 30 minutes, annealing at 130°C for 1 hour, and naturally cooling to obtain a proton exchange membrane.
[0074] Comparative Example 3
[0075] The preparation of the proton exchange membrane of this comparative example is as follows:
[0076] (1) Weigh 1 mmol of 4,4'-diamino-2,2'-bipyridine, add it to 100 ml of ethanol aqueous solution with a mass ratio of 1:1, heat it in a 60°C water bath, stir it for 12 hours, and then centrifuge it at a centrifugal speed of 5000 r / min for 10 minutes, then filter it and wash it with water for 3 times, and finally dry it at 60°C for 2 hours to obtain an additive.
[0077] (2) Add 10 g of perfluorosulfonic acid resin to a mixed solvent of 6 g of water, 6 g of n-propanol, and 3 g of N,N-dimethylformamide, and stir for 24 h to obtain a uniform perfluorosulfonic acid solution. Add 0.1 g of the additive to the perfluorosulfonic acid solution, stir for 12 h, and then place it in an ultrasonic cleaning machine for 30 min to disperse it evenly, thereby obtaining a perfluorosulfonic acid resin solution containing the additive.
[0078] (3) The reinforced layer polyetheretherketone (PEEK) mesh was placed in a plasma cleaning machine for treatment. The treatment time was 100 s, the power was 100 W, the gas was nitrogen, and the gas flow rate was 200 mL / min.
[0079] (4) The perfluorosulfonic acid resin solution containing the additive is placed in a coating machine for the first coating, followed by bonding to a polyetheretherketone (PEEK) mesh cloth, drying at 60°C for 30 minutes, and then coating for the second time, drying at 60°C for 30 minutes, annealing at 130°C for 1 hour, and naturally cooling to obtain a proton exchange membrane.
[0080] Performance Testing
[0081] (1) Chemical durability test
[0082] 8ppm Fe 2+ (0.00366 g of ferrous sulfate heptahydrate) was added to 100 mL of 30 wt% H 2 O 2 Then, a 4 cm × 4 cm proton exchange membrane (weighed dry weight m) was placed in a 80°C water bath. dry ) was immersed in Fenton's reagent for 16 hours, and the degree of corrosion of the proton exchange membrane was tested by calculating the mass difference before and after treatment, so as to judge the chemical stability of the proton exchange membrane.
[0083] (2) Tensile strength
[0084] The tensile strength of the proton exchange membrane was tested using GB / T 20042.32009 Proton exchange membrane fuel cell part 3: proton exchange membrane test method.
[0085] (3) Proton conductivity
[0086] The proton conductivity of the proton exchange membrane was tested using "GB / T20042.3-2009 Proton Exchange Membrane Fuel Cell Part 3: Proton Exchange Membrane Test Method" under the conditions of 80°C and 100% RH.
[0087] Table 1
[0088]
[0089] First, by comparing Comparative Examples 1 to 3, it can be seen that replacing part of the perfluorosulfonic acid resin in the proton exchange membrane with carboxylated cerium oxide can improve chemical stability, but reduce tensile strength and proton conductivity; it can be seen that replacing part of the perfluorosulfonic acid resin in the proton exchange membrane with 4,4'-diamino-2,2'-bipyridine can simultaneously improve chemical stability and slightly improve tensile strength and proton conductivity. However, further comparing Comparative Examples 1 to 3 with Example 1 shows that the degree of chemical stability and the degree of tensile strength and proton conductivity improved by replacing part of the perfluorosulfonic acid resin in the proton exchange membrane with carboxylated cerium oxide and 4,4'-diamino-2,2'-bipyridine simultaneously exceed the expected degree of replacing part of the perfluorosulfonic acid resin in the proton exchange membrane with only carboxylated cerium oxide and replacing part of the perfluorosulfonic acid resin in the proton exchange membrane with only 4,4'-diamino-2,2'-bipyridine. That is to say, replacing part of the perfluorosulfonic acid resin in the proton exchange membrane with carboxylated cerium dioxide and 4,4'-diamino-2,2'-bipyridine simultaneously can achieve synergistic improvements in the chemical stability, tensile properties and proton conductivity of the proton exchange membrane.
[0090] In addition, by comparing Comparative Example 1 with Examples 2 to 4, it can be seen that replacing part of the perfluorosulfonic acid resin in the proton exchange membrane with other types of inorganic free radical quenchers and other types of organic antioxidants can improve chemical stability and increase tensile strength and proton conductivity.
[0091] Finally, see Figure 2 It can be seen that after the plasma treatment, the PEEK mesh reinforcement layer can improve the bonding effect with the perfluorosulfonic acid resin layer, that is, after the plasma treatment, the PEEK mesh reinforcement layer will be completely filled with perfluorosulfonic acid resin. This means that the reinforcement layer after the plasma treatment has a better bonding effect with the perfluorosulfonic acid resin layer, and the bonding is tighter and has fewer defects.
[0092] The above contents involving common knowledge are not described in detail, and those skilled in the art can understand them.
[0093] The above descriptions are only some specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention shall be included in the protection scope of the present invention. The technical scope of the present invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.
Claims
1. A composite proton exchange membrane, characterized in that: include: A reinforcing layer and a coating layer are formed on at least one side of the reinforcing layer, and the coating layer includes perfluorosulfonic acid resin, inorganic free radical quencher, and organic antioxidant.
2. The composite proton exchange membrane according to claim 1, characterized in that: The inorganic free radical quencher includes a carboxylated inorganic free radical quencher, and the organic antioxidant includes an organic antioxidant with an amino group.
3. The composite proton exchange membrane according to claim 2, characterized in that: The inorganic free radical quencher includes one or more of carboxyl cerium dioxide and carboxyl manganese dioxide, and the organic antioxidant includes one or more of 4,4'-diamino-2,2'-bipyridine and 3,4-dihydroxyphenylalanine.
4. The composite proton exchange membrane according to claim 1, characterized in that: The molar ratio between the inorganic free radical quencher and the organic antioxidant is 1:(0.2 to 3).
5. The composite proton exchange membrane according to claim 1, characterized in that: The total mass of the inorganic free radical quencher and the organic antioxidant is 0.02 g to 0.5 g per 10 g of the perfluorosulfonic acid resin.
6. The composite proton exchange membrane according to claim 1, characterized in that: The reinforcement layer is plasma treated, and includes one of polyetheretherketone (PEEK), polytetrafluoroethylene (PTFE), and polyphenylene sulfide (PPS).
7. A method for preparing a composite proton exchange membrane, characterized in that: include: A coating is provided, the coating comprising a perfluorosulfonic acid resin, an inorganic free radical quencher, and an organic antioxidant; Applying the coating to at least one side of a reinforcement layer; as well as The coating material applied to the reinforcing layer is dried and annealed to form a coating layer.
8. The method for preparing a composite proton exchange membrane according to claim 7, characterized in that: The preparation of the coating comprises: Mixing the inorganic free radical quencher with a first solvent to obtain a mixed solution; mixing the organic antioxidant with the mixed solution; Drying the mixed solution containing the organic antioxidant to obtain an additive; mixing the perfluorosulfonic acid resin with a second solvent to obtain a perfluorosulfonic acid solution; and The additive is mixed with the perfluorosulfonic acid solution to obtain the coating.
9. The method for preparing a composite proton exchange membrane according to claim 7, characterized in that: Before applying the coating to the reinforcing layer, the method further includes: treating the reinforcing layer with plasma, wherein the plasma treatment time is 50s to 500s, the power is 50W to 300W, the gas introduced is nitrogen, and the gas flow rate is 50mL / min to 200mL / min.
10. The method for preparing a composite proton exchange membrane according to claim 7, characterized in that: The drying temperature is 60° C. to 100° C., and the time is 30 min to 120 min. The annealing temperature is 100° C. to 160° C., and the time is 30 min to 120 min.